Sustainable development: as a whole of stability and instability (Synergetic analysis) (Zien Journal of Social Sciences and Humanities, 2022)
In this paper, the order resulting from the integration of stability with instability is shown in a systematic form. The synergetic method of forming a picture of the relations of man, nature, and society in the context of globalization explains the essence. It is guaranteed that the definition of chaos will bring a positive result. This shows that it plays an important role in revealing the essence of the problems that are especially relevant to all sectors of society. In particular, it defines the function of the methodological basis as a solution to the problems of the rise and fall of ecological, social, economic, political, spiritual, medical systems. It focuses on the importance of knowing the importance of big and small elements in any situation in the development of a society